2012
DOI: 10.1007/s11103-012-9988-9
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of a selectable marker gene in the doubled haploid progeny of co-transformed barley plants

Abstract: Following the production of transgenic plants, the selectable marker gene(s) used in the process are redundant, and their retention may be undesirable. They can be removed by exploiting segregation among the progeny of co-transformants carrying both the selectable marker gene and the effector transgene. Here we show that the doubled haploid technology widely used in conventional barley breeding programmes represents a useful means of fixing a transgene, while simultaneously removing the unwanted selectable mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…For the cotransformation, site-specific recombination, and other T-DNA-based strategies for marker gene removal (Ebinuma et al, 2001;Wang et al, 2011;Kapusi et al, 2013;Yau and Stewart, 2013), the complex transgene integration patterns such as multiple T-DNA loci, tandem-linked T-DNA copies, T-DNA truncations, and cotransferred non-T-DNA vector backbone sequence in transgenic plants (Kim et al, 2003;Rai et al, 2007) may complicate the molecular analysis of transgene integration and affect the stability of transgene expression. In this study, we validated that the maize Ac/Ds transposable element can be routinely used to generate marker-free transgenic plants in rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the cotransformation, site-specific recombination, and other T-DNA-based strategies for marker gene removal (Ebinuma et al, 2001;Wang et al, 2011;Kapusi et al, 2013;Yau and Stewart, 2013), the complex transgene integration patterns such as multiple T-DNA loci, tandem-linked T-DNA copies, T-DNA truncations, and cotransferred non-T-DNA vector backbone sequence in transgenic plants (Kim et al, 2003;Rai et al, 2007) may complicate the molecular analysis of transgene integration and affect the stability of transgene expression. In this study, we validated that the maize Ac/Ds transposable element can be routinely used to generate marker-free transgenic plants in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been developed to remove selectable markers from transgenic plants while retaining the gene of interest (GOI; Ebinuma et al, 2001;Cotsaftis et al, 2002;Wang et al, 2011;Kapusi et al, 2013;Yau and Stewart, 2013;Oliva et al, 2014). Transposition is an advantageous strategy for marker gene removal, because it allows intact transgene insertion with defined boundaries and requires only a few primary transformants (Cotsaftis et al, 2002).…”
mentioning
confidence: 99%
“…Another strategy aims at androgenetic generation (haploid technology) of a segregating population of homozygous plants raised from pollen of primary transgenic barley plants produced via Agrobacterium infection of immature embryos. The results demonstrated that selectable marker-free homozygous transgenic plants can be effi ciently generated (Coronado et al 2005 ;Kapusi et al 2013 ). However, even though haploid technology represents an elegant solution and accelerates time and resource effi ciency of generating true-breeding, selectable markerfree transgenic barley, the major limitation is its strong genotype dependency.…”
Section: Marker Gene Eliminationmentioning
confidence: 95%
“…[13]. Microspores of tobacco, rapeseed, wheat, and barley are exploited in transformation and mutagenesis programs, in order to fix mutations and transgenes in a single step through subsequent DH induction [38][39][40][41][42]. For example in Brassicas, microspore mutation studies have enabled modifications of disease resistance, cold tolerance, and fatty acid composition [43].…”
Section: Haploids and Doubled Haploids: Their Production And Use In Bmentioning
confidence: 99%